2020
DOI: 10.1002/ajmg.a.61982
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐specific facial dysmorphism in Axenfeld‐Rieger syndrome caused by FOXC1 and PITX2 variants

Abstract: Axenfeld-Rieger syndrome is a genetic condition characterized by ocular and systemic features and is most commonly caused by variants in the FOXC1 or PITX2 genes. Facial dysmorphism is part of the syndrome but the differences between both genes have never been systematically assessed. Here, 11 facial traits commonly reported in Axenfeld-Rieger syndrome were assessed by five clinical geneticists blinded to the molecular diagnosis. Individuals were drawn from the Australian and New Zealand Registry of Advanced G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, systemic features were present in more than half of the patients with FOXC1 variants, but in all individuals with PITX2 variants, and this has been reported on an overlapping set of ANZRAG patients in the past. 31,43 It has been previously reported that while the systemic features are variably expressed between both genes, the ocular features are believed to be similar between both genes. Tumer et al, Strungaru et al, and D'Haene et al previously reported phenotypic differences between the FOXC1 and PITX2 variants, both associated with ARS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, systemic features were present in more than half of the patients with FOXC1 variants, but in all individuals with PITX2 variants, and this has been reported on an overlapping set of ANZRAG patients in the past. 31,43 It has been previously reported that while the systemic features are variably expressed between both genes, the ocular features are believed to be similar between both genes. Tumer et al, Strungaru et al, and D'Haene et al previously reported phenotypic differences between the FOXC1 and PITX2 variants, both associated with ARS.…”
Section: Discussionmentioning
confidence: 99%
“…35 In a similar vein, while craniofacial dysmorphism was not observed on MR imaging of the brain in any of the individuals included in our case series, features such as thin upper lip and maxillary hypoplasia were reported in 78% of individuals with FOXC1 variants and 93% of individuals with PITX2 variants in 1 previous study, 35 and in another study (which included all cases described here), hypertelorism/telecanthus and low-set ears were found to be more prevalent in those with FOXC1 variants compared with those with PITX2 variants. 15 This case series was limited by its small cohort size (n ¼ 12), particularly with respect to the PITX2 variant group (n ¼ 2), which like other ARS case series precluded statistical comparisons. 33…”
Section: Cerebellummentioning
confidence: 98%
“…9,10 Pathogenic and likely pathogenic variants in FOXC1 and PITX2 have been reported in 40% of individuals with a clinical diagnosis of ARS, 11,12 with unique ocular and systemic phenotypes associated with each gene. [13][14][15][16] Variants in both FOXC1 and PITX2 have also been associated with a range of CNS malformations, including hydrocephalus, [16][17][18] classic commissural agenesis (corpus callosum agenesis), [17][18][19] and cerebellar malformations (Dandy-Walker phenotype, 20 mega cisterna magna, and cerebellar vermis hypoplasia). 18,21,22 More recently, cerebral small-vessel disease has been reported in individuals with FOXC1 or PITX2 variants, with the presence of WM hyperintensities, dilated perivascular spaces, and lacunar infarcts on MR imaging.…”
mentioning
confidence: 99%